Implementasi Metode Tutor Sebaya Melalui Pemanfaatan Media Kantong Ajaib dalam Keterampilan Membaca di MTs Darussalam Sleman - Fitria, Hanna Sajida; Arif, Agus Alfaya (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Reading skills play a crucial role in the learning process, yet many students still struggle to comprehend Arabic texts effectively. This study examines the implementation of the Peer Tutor method supported by the Magic Pocket media to enhance students’ reading abilities at MTs Darussalam. The Peer Tutor method enables collaborative learning, allowing students to assist one another in understanding reading materials, while the Magic Pocket media containing various learning tools related to Arabic texts helps create a more engaging and interactive learning environment. Using a qualitative approach, data were collected through interviews, observations, and documentation to capture the experiences and perceptions of teachers and students. The findings reveal that the Peer Tutor method encourages active knowledge sharing, and the Magic Pocket media significantly increases student interest and participation in the learning process. Together, these components contribute to improved reading skills among students. The study concludes that integrating the Peer Tutor method with Magic Pocket media offers an effective alternative strategy for enhancing Arabic reading proficiency and recommends its broader application in similar educational settings.